Development of finite-element models of human skeleton bones and their application to the natural vibration problem - Matveenko, Valeriy Pavlovich; Shardakov, Igor Nikolaevich; Shestakov, Alexey Petrovich (Computational Continuum Mechanics, 2012)
The capabilities of the previously developed algorithm for finite-element modeling of human body parts are demonstrated on tomographic measurement data. The obtained tomographic images of human shin bones, skull bones and pelvic bones are used to solve the problem of searching for eigenmodes and eigenfrequencies of vibrations of human skeleton bones by the finite-element method.
Keywords: tomographic measurements; human skeleton bones; finite element method; eigenmodes